2005
DOI: 10.1111/j.1398-9995.2005.00945.x
|View full text |Cite
|
Sign up to set email alerts
|

Fast foods – are they a risk factor for asthma?

Abstract: Frequent consumption of hamburgers showed a dose-dependent association with asthma symptoms, and frequent takeaway consumption showed a similar association with BHR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
104
3
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(122 citation statements)
references
References 23 publications
10
104
3
5
Order By: Relevance
“…Numerous epidemiological studies have been conducted to investigate the association between dietary habits and the risk of asthma in children. These studies have identified the intake of fruits, vegetables and fish as protective factors against childhood asthma while fast food consumption as a risk factor for the disease [6][7][8][9][10][11]. Studies on dietary habits and severity of asthma are few and show reconsistent results [11][12][13].…”
Section: R R R R R E E E E E S S S S S E E E E E a A A A A R R R R R mentioning
confidence: 99%
“…Numerous epidemiological studies have been conducted to investigate the association between dietary habits and the risk of asthma in children. These studies have identified the intake of fruits, vegetables and fish as protective factors against childhood asthma while fast food consumption as a risk factor for the disease [6][7][8][9][10][11]. Studies on dietary habits and severity of asthma are few and show reconsistent results [11][12][13].…”
Section: R R R R R E E E E E S S S S S E E E E E a A A A A R R R R R mentioning
confidence: 99%
“…Interventions with supplementation of a single nutrient have been disappointing (3)(4)(5), and it may be important to consider the diet as a whole to understand the possible synergistic effects of various food components. Several studies have shown that asthma outcomes were negatively associated with citrus fruits (6), apples, pears (7)(8)(9), tomato, carrots, leafy vegetables (7), butter, whole milk (9) and nonpasteurized farm milk (10), and positively associated with fast foods (11). However, studies addressing the associations between different dietary patterns and asthma are still lacking.…”
mentioning
confidence: 99%
“…Wickens ve ark.nın, Yeni Zellanda'da astım ve "fast-food" tüketimi arasındaki ilişkiyi inceledikleri çalışmada, tüketilen hamburger miktarı ve astım arasında pozitif yönlü bir ilişki olduğu saptanmıştır. 7 İnanç'ın yaptığı başka bir çalışmada ise astımlı çocukların hamburger, şekerleme, cips yeme, gazlı içecek içme oranlarının astım hastası olmayanlara göre yüksek olduğu görülmüştür. 8 …”
Section: Astim Ve Beslenmeunclassified